1,3,4-oxadiazoles as inhibitors of the atypical member of the BET family bromodomain factor 3 from Trypanosoma cruzi (TcBDF3) - Alonso, Victoria L.; Escalante, Andrea M.; Rodríguez Araya, Elvio; Frattini, Gianfranco; Tavernelli, Luis E.; Moreno, Diego M.; Furlan, Ricardo L. E.; Serra, Esteban (Frontiers in Microbiology, 2024)
Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, affects millions globally with increasing urban cases outside of Latin America. Treatment in based on two drugs: benznidazole and nifurtimox, but chronic cases pose several challenges. Targeting lysine acetylation, particularly bromodomain-containing proteins, shows promise as a novel antiparasitic target. Our research focuses on TcBDF3, a cytoplasmic protein crucial for parasite differentiation that recognizes acetylated alpha-tubulin. In previous work, A1B4 was identified as a high-affinity binder of TcBDF3, showing significant trypanocidal activity with low host toxicity in vitro. In this report, the binding of TcBDF3 to A1B4 was validated using differential scanning fluorescence, fluorescence polarization, and molecular modeling, confirming its specific interaction. Additionally, two new 1,3,4-oxadiazoles derived from A1B4 were identified, that exhibit improved trypanocide activity and cytotoxicity profiles. Furthermore, TcBDF3 was classified for the first time as an atypical divergent member of the Bromodomain Extra-Terminal family found in protists and plants. These results make TcBDF3 a unique target due to its localization and known functions not shared with higher eukaryotes, which holds promise for Chagas disease treatment.